A Method to Reduce Air Heating Costs in Winter Period in The Królowa Luiza Mining Museum in Zabrze - Case Study - Słota, Krzysztof; Słota, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Królowa Luiza Mining Museum is one of the touristic objects of the Coal Mining Museum in Zabrze. In the study in concern, an assessment of ventilation of the facility was conducted. Following the assessment of the ventilation, the operating parameters of the fans were changed, inlets were sealed and a system of air ducts was designed and constructed. The ducts reintroduce the heated air from the facility to workings.
Keywords: Mining Museum in Zabrze; tourist traffic; air heating; reducing costs; ventilation; recuperation; Muzeum Górnictwa w Zabrzu; ruch turystyczny; ogrzewanie powietrza; obniżenie kosztów; wentylacja; rekuperacja